Molecules to Mountains: A Multi-Proxy Investigation Into Ancient Climate and Topography of the Pacific Northwest, USA - McLean, Alexander; Bershaw, John (Frontiers in Earth Science, 2021)
We characterize the topographic evolution of the Pacific Northwest, United States, during the Cenozoic. New paleosol carbonate stable isotope (δ18O) results from central Oregon are presented, along with published proxy data, including fossil teeth, smectites, and carbonate concretions. We interpret a polygenetic history of Cascade Mountain topographic uplift along-strike, characterized by: 1) Steady uplift of the Washington Cascades through the Cenozoic due long-term arc rotation and shortening against a Canadian buttress, and 2) Uplift of the Oregon Cascades to similar-to-modern elevations by the late Oligocene, followed by topographic stagnation as extension developed into the Neogene. Since the Miocene, meteoric water δ18O values have decreased in Oregon, possibly due to emergence of the Coast Range and westward migration of the coastline. Spatial variability in isotopic change throughout the Pacific Northwest suggests that secular global climate change is not the primary forcing mechanism behind isotopic trends, though Milankovitch cycles may be partly responsible for relatively short-term variation.